Microencapsulation of bixin pigment by spray drying: Evaluation of characteristics. (June 2021) - Balakrishnan, M.; Gayathiri, S.; Preetha, P.; Pandiselvam, R.; Jeevarathinam, G.; Delfiya, D.S. Aniesrani; Kothakota, Anjineyulu
Abstract: The present work was conducted to microencapsulate the commercial (CE), and solvent (SE) extracted annatto using modified starch (MS) and gelatine (G) blend as wall material by spray drying. The conditions used were solid: liquid (S/L) ratio 1:10, extraction temperature 70 °C, and extraction time interval (10–35 min) for the SE annatto extract. Among the different treatments, 20 min extraction time was highly significant in the recovery of 93.19 ± 0.06 g/100 g of annatto seeds of total pigment and 94.78 ± 0.89% of bixin recovery. Both SE and CE annatto extracts have been used as a core material with wall materials (MS: G) in varied ratios of 100:0 to 60:40 to produce the microcapsules. The highest encapsulation efficiency of 86.18% and 86.37% were recorded for the SE and CE microcapsules prepared with the wall material (MS: G) ratio of 60:40. Encapsulated extract recorded higher stability against light, oxygen, and heat than the non-encapsulated annatto. In vitro release study of both microcapsules in three different pH conditions (1.2, 6.8, and 7.4) revealed an initial burst release of bixin pigment followed by a controlled release of bixin from microcapsules. Highlights: The highest encapsulation efficiency 86.37% was recorded for the commercial annatto extract microcapsules. The encapsulated particle size ranged from 1 to 7.2 μm with spherical shape. Encapsulated extract recorded higher stability against light, oxygen and heat. In vitro release study of the bixin pigment shows that initial burst release followed by a controlled release.